Антология выдающихся достижений в науке и технике. Часть 27: Портрет харьковского математика Наума Ильича Ахиезера - Баранов, М.И. (Електротехніка і електромеханіка, 2015)
Приведен краткий научно-исторический очерк об известном математике Харьковщины − член-корреспонденте
АН УССР Ахиезере Н.И. и его выдающемся вкладе в мировую математическую науку. Наведено короткий науково-історичний нарис про відомого математика Харківщини − член-кореспондента АН УРСР
Ахиезера Н.І. і його видатний внесок в світову математичну науку. Purpose. Description in brief of basic scientific achievements,
features of personality and way of life of the known Kharkov
mathematician Akhiezer N.I. Methodology. Existent scientific
approaches for treatment and systematization of mathematical
knowledges. Methods of historical method at research of development in society of such sections of mathematics as a theory of functions, functional analysis and integral equations.
Results. Short information is presented about the basic creative and vital stages, and also fundamental scientific achievements indicated prominent mathematicians of the 20-th century. Some personal qualities of this remarkable Kharkov
mathematician, leaving about itself kind memory for thankful
descendants are described. Originality. First a scientistelectrophysicist for the wide circle of readers imagined a short
scientifically-historical essay on the known mathematician of
contemporaneity, being based on his scientific labours and
published materials about him. Practical value. Scientific
popularization of the known Kharkov mathematician and his
achievements in the area of theory of functions and mathematical physics. Next philosophical reminder a wide reader on
the example of life and prominent scientific results of labour of
one known human personality about incessant in society connection of times and generations.